Scientific foundations of clinical assessment - Haynes, Stephen N.; Smith, Greg (Gregory T.); Hunsley, John, 1959- (New York, NY : Routledge, 2019)
Scientific Foundations of Clinical Assessment is a user-friendly overview of the most important principles and concepts of clinical assessment. It provides readers with a science-based framework for interpreting assessment research and making good assessment decisions, such as selecting the best instruments and measures and interpreting the obtained assessment data. Written in a direct and highly readable fashion, with plenty of clinical examples that illustrate the relevance of psychometric principles and assessment research, this text is one every professional and graduate student needs to read. The second edition is expanded and fully updated, and includes additional coverage of the principles and methods of developing new assessment instruments.
Introduction to the scientific foundations of clinical assessment -- Reliability of clinical assessment measures -- Validity of clinical assessment measures -- Applying psychometric evidence to clinical judgments -- How to evaluate commonly used statistical methods and outcomes -- The contributions of factor analysis to clinical assessment -- The utility of science-based clinical assessment -- The conditional and dynamic nature of psychometric evidence -- Using data from multiple sources in clinical assessment.
Includes bibliographical references and indexes.
Print version record and CIP data provided by publisher; resource not viewed.
Stephen N Haynes is an Emeritus Professor of Psychology at the University of Hawai'i at Måanoa in Clinical Psychology. Dr. Haynes was previously the Director of Clinical Psychology and Department Chair in psychology. He was editor of the APA journal Psychological Assessment, has served on 14 editorial boards, and has published 8 books and 130 articles and chapters on clinical assessment and psychopathology. Gregory T Smith is a Professor of Psychology and University Research Professor at the University of Kentucky. He has published over 200 research articles and book chapters, the majority of which focus on clinical psychological assessment. He served for 12 years as the director of the doctoral program in clinical psychology at the University of Kentucky and is now Chair of the Psychology Department there. John Hunsley is a Professor of Psychology and Director of the Clinical Psychology Program in the School of Psychology at the University of Ottawa. He published over 130 articles, chapters, and books related to assessment, evidence-based practice, and professional issues in psychology.
Master record variable field(s) change: 072
Keywords: Psychological tests -- Methodology; Psychodiagnostics -- Methodology; Psychological Tests